Integrin signaling regulates spindle orientation in Drosophila to preserve the follicular-epithelium monolayer. - Fernández-Miñán, A.; Martín-Bermudo, M.D.; González-Reyes, A. (Current Biology, 2007)
Epithelia act as important physiological barriers and as structural components of tissues and organs. In the Drosophila ovary, follicle cells envelop the germline cysts to form a monolayer epithelium. During division, the orientation of the mitotic spindle in follicle cells is such that both daughter cells remain within the same plane, and the simple structure of the follicular epithelium is thus preserved. Here we show that integrins, heterodimeric transmembrane receptors that connect the extracellular matrix to the cell's cytoskeleton [1, 2], are required for maintaining the ovarian monolayer epithelium in Drosophila. Mosaic egg chambers containing integrin mutant follicle cells develop stratified epithelia at both poles. This stratification is due neither to abnormal cell proliferation nor to defects in the apical-basal polarity of the mutant cells. Instead, integrin function is required for the correct orientation of the mitotic apparatus both in mutant cells and in their immediately adjacent wild-type neighbors. We further demonstrate that integrin-mediated signaling, rather than adhesion, is sufficient for maintaining the integrity of the follicular epithelium. The above data show that integrins are necessary for preserving the simple organization of a specialized epithelium and link integrin-mediated signaling to the correct orientation of the mitotic spindle in this epithelial cell type.